2016
DOI: 10.3109/07853890.2015.1131327
|View full text |Cite
|
Sign up to set email alerts
|

BDNF in sleep, insomnia, and sleep deprivation

Abstract: The protein brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin family of growth factors involved in plasticity of neurons in several brain regions. There are numerous evidence that BDNF expression is decreased by experiencing psychological stress and that, accordingly, a lack of neurotrophic support causes major depression. Furthermore, disruption in sleep homeostatic processes results in higher stress vulnerability and is often associated with stress-related mental disorders. Recently, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(129 citation statements)
references
References 97 publications
10
118
0
1
Order By: Relevance
“…In the present study, BDNF concentrations were elevated from 0H to 12H, and continued to stay elevated at 24H. Previous research has shown that chronic periods of stress, sleep disturbance, and military training lead to a downregulation of BDNF expression (Suzuki et al 2014), however acute periods of stress (e.g., sleep deprivation, caloric deficit, and physical exertion) may increase the BDNF response (Gronli et al 2013;Huang et al 2014;Schmitt et al 2016). BDNF plays an essential role in cognitive function and memory (Erickson et al 2010), and transient increases in BDNF may explain the maintenance of some aspects of cognitive function during the SUSOP.…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, BDNF concentrations were elevated from 0H to 12H, and continued to stay elevated at 24H. Previous research has shown that chronic periods of stress, sleep disturbance, and military training lead to a downregulation of BDNF expression (Suzuki et al 2014), however acute periods of stress (e.g., sleep deprivation, caloric deficit, and physical exertion) may increase the BDNF response (Gronli et al 2013;Huang et al 2014;Schmitt et al 2016). BDNF plays an essential role in cognitive function and memory (Erickson et al 2010), and transient increases in BDNF may explain the maintenance of some aspects of cognitive function during the SUSOP.…”
Section: Discussionsupporting
confidence: 57%
“…These authors hypothesized a mediating role in the link between stress experience and serum BDNF levels in these individuals (Giese et al., , ). These findings, obtained from clinical samples, are supported by experimental studies showing reduced BDNF levels in subjects with prolonged sleep deprivation (Meerlo et al., ; Schmitt, Holsboer‐Trachsler, & Eckert, ). Meerlo et al.…”
Section: Methodssupporting
confidence: 58%
“…Taken together, our data indicate that low sleep stage N3 and REM sleep, independent of a specific sleep disorder, are related to low BDNF. These findings extend the increasingly acknowledged impact of an interplay between stress and sleep on BDNF levels (Schmitt et al ., ).…”
Section: Discussionmentioning
confidence: 97%